2014
DOI: 10.4103/0976-9668.136186
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting compliance to management of diabetes in Urban Health Center of a tertiary care teaching hospital of south India

Abstract: Aim:To Study the Factors affecting compliance to diabetes management and study risk factors and complications of type II diabetes.Settings and Design:Primary health center, Descriptive study.Materials and Methods:A descriptive study of previously diagnosed diabetics (n = 135) attending the chronic disease clinic of Urban Health Center, Jawaharlal Institute of Postgraduate Medical Education and Research (JIUHC) was carried out during October 2011 to December 2011. Data were collected by personal interview on de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 6 publications
0
12
2
1
Order By: Relevance
“…Thus, compliance appeared to be the most predominant factor for maximizing bone benefits [ 22 ]. Factors affecting compliance are numerous and should be taken into account in lifestyle interventions [ 36 ]. We report that all sites (total body, lumbar spine and femoral neck, for both BMC and BMD) in compliant participants benefited from the training, whereas previous literature has commonly reported site-specific improvements [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, compliance appeared to be the most predominant factor for maximizing bone benefits [ 22 ]. Factors affecting compliance are numerous and should be taken into account in lifestyle interventions [ 36 ]. We report that all sites (total body, lumbar spine and femoral neck, for both BMC and BMD) in compliant participants benefited from the training, whereas previous literature has commonly reported site-specific improvements [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 Two studies from Southern India reported 24% compliance in hypertension and 76% compliance in diabetes. 14 , 15 For antihypertensive therapy, compliance has been shown to vary from 73% in Southern India to 23% in Northern India. 16 , 17 The compliance was noted to be good in most participants of our study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] Santhanakrishnan et al observed compliance to oral hypoglycemic agents in 76% subjects, dietary modifications in 81.4% and physical activity in 37% subjects from Puducherry, India. [ 12 ] While in the current study, pharmacological compliance was reported by 76.2% participants and compliance to the non-pharmacological management was reported by 50.8% participants. The results observed by us were similar to the above-mentioned findings.…”
Section: Discussionmentioning
confidence: 52%
“…Pharmacological compliance was self-reported, with participants reporting to have missed more than two doses in last 15 days were considered as non-compliant. [ 12 ] Non-pharmacological compliance means adherence to the measures like diet modification and exercises. Due to lack of exact definition of compliance to the non-pharmacological management, a scale was developed with equal importance to diet modifications and physical exercises.…”
Section: Methodsmentioning
confidence: 99%